Analysis of Factors Associated with the Healing Status of Pulmonary Tuberculosis Patients at Puskesmas Perumnas 1 Pontianak in 2018 - Christa Adelia Suvianto; Hadiyanto (Sriwijaya Journal of Medicine, 2020)
Factors Related to the Healing Status of Patients with Pulmonary Tuberculosis in Puskesmas Perumnas 1 Pontianak 2018. Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis that is still a global health problem. The healing of patients from TB is important to note because it can harm public health such as providing opportunities for TB disease transmission to family members and the surrounding community, thereby increasing the spread of disease and deaths due to TB. The recovery of TB patients is influenced by several factors such as age, sex, level of education, knowledge, level of income, access to health services, the role of PMO and treatment compliance. This study aims to determine the factors associated with the healing status of TB sufferers. This type of research is analytic descriptive with a cross-sectional design. The instruments used were questionnaires and patient medical records. Data were obtained by interviewing 106 pulmonary TB patients at their home who had been treated with category 1 treatment for 6 months in Perumnas 1 Health Center in Pontianak City. The results of Chi-square test showed that gender (p=0.005), level of education (p=0.002), knowledge (p=0.008), the role of PMO (p=0.001) and medication adherence (p=0.000) are related to the healing status of TB sufferers, while age (p=0.320), income level (p=0.728) and access to health services (p=0.141) are not related to the healing status of TB sufferers. Counseling about factors related to TB recovery is expected to increase the cure rate of TB patients.